Application of Natural Zeolite for the Removal of Diethylenetriamine (DETA) and DETA-Metal Complexes from Flotation Process Water (The Australasian Institute of Mining and Metallurgy, 2010)
Application of Natural Zeolite for the Removal of Diethylenetriamine (DETA) and DETA-Metal Complexes from Flotation Process Water